2019
DOI: 10.1186/s40634-019-0189-1
|View full text |Cite
|
Sign up to set email alerts
|

Histological incorporation of acellular dermal matrix in the failed superior capsule reconstruction of the shoulder

Abstract: Background Superior capsule reconstruction addresses massive rotator cuff tears using allografts and aims to restore the natural superior constraint of the shoulder and therefore shoulder biomechanics and function. There is no evidence relating to the histological incorporation of these grafts. Methods 27 superior capsule reconstructions were performed between June 2016 and November 2017. Follow-up was with clinical assessment and Magnetic Resonance Imaging, to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…The overall rate of complications post-SCR ranged from 5.0% to 70.0% (I 2 ¼ 77.3%; Fig 2) (507 shoulders; Table 2). [36][37][38]44,51,52,[58][59][60][61][62][63][64][65] The complication rate in the 8 studies using allografts (289 shoulders) [36][37][38]44,51,59,62,65 ranged from 5% to 70% (I 2 ¼ 84.9%) while the complication rate of the 4 studies using autografts (176 shoulders) 52,58,63,64 ranged from 14% to 32% (I 2 ¼ 42.1%).…”
Section: Resultsmentioning
confidence: 99%
“…The overall rate of complications post-SCR ranged from 5.0% to 70.0% (I 2 ¼ 77.3%; Fig 2) (507 shoulders; Table 2). [36][37][38]44,51,52,[58][59][60][61][62][63][64][65] The complication rate in the 8 studies using allografts (289 shoulders) [36][37][38]44,51,59,62,65 ranged from 5% to 70% (I 2 ¼ 84.9%) while the complication rate of the 4 studies using autografts (176 shoulders) 52,58,63,64 ranged from 14% to 32% (I 2 ¼ 42.1%).…”
Section: Resultsmentioning
confidence: 99%
“…Eight of these 9 studies reported a revision rate of 4% or less. ** In contrast, of the 16 clinical studies of ASCR that used allografts or xenografts published to date that reported a minimum follow-up of 6 months to 2 years, †† only 4 studies 13 , 29 , 41 , 50 reported an MRI evaluation of graft integrity for each of the enrolled patients, and the calculated graft tear proportion ranged from 18.5% to 50% in the first 6 to 12 months of follow-up. In the remaining 12 studies of ASCR that used allografts or xenografts, a selected subgroup of patients underwent MRI evaluation, resulting in a proportion that reflects only this selected subgroup’s graft tear rate.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed that SCR is a successful treatment for irreparable rotator cuff tears in the short term based on patient-reported outcome scores, MRI, and plain radiographs. 3,7,8,10,15 Aside from a few case reports, there has been a paucity of direct confirmation regarding the integration and recellularization of the ADM. 2,7,16,17 This case series examined the histology of whole or large segments of SCR explants from 8 patients of a wide age range, as well as from a multitude of time points after implantation. It represents a significant advancement in our knowledge regarding biologic incorporation of ADMs used in SCR.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in a small case series, Ravencroft et al 17 followed 27 total patients who had SCR in 2016-2017. During follow-up MRIs, 5 procedures were labeled as failures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation